2021
DOI: 10.1016/j.indmarman.2020.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Digital servitization: Crossing the perspectives of digitization and servitization

Abstract: For over three decades now, several product companies around the world have been undertaking servitization paths. They have been devoting growing and substantial efforts to expand their service business. Expanding the service business in addition to their traditional core product business secures long-term growth and strengthens competitive advantages in business-to-business marketplaces. Recently, service business expansion has taken up many of the new digital technologies offered through the digital transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
162
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(169 citation statements)
references
References 32 publications
(27 reference statements)
5
162
0
2
Order By: Relevance
“…Recent studies view digitalization of manufacturing as closely related to servitization transformation (Kohtamäki et al, 2020). In particular, the emerging literature on digital servitization shows that digital technologies allow manufacturers to provide new value creation and value capture opportunities through monitoring, control, optimization, and autonomous functions (Gebauer et al, 2020;Kohtamäki et al, 2019;Paschou et al, 2020). In other words, digital technologies not only facilitate servitized business models (Arnold et al, 2016;Suppatvech et al, 2019;Vendrell-Herrero et al, 2017), such as outcome business models (Sjödin et al, 2020a;Visnjic et al, 2017) but also contribute to the development of emerging industrial digital platforms with opportunities for value creation and capture that go far beyond traditional products and services (Cenamor et al, 2017;Rajala et al, 2019;Wei et al, 2019).…”
Section: Digital Servitization and Industrial Digital Platformsmentioning
confidence: 99%
“…Recent studies view digitalization of manufacturing as closely related to servitization transformation (Kohtamäki et al, 2020). In particular, the emerging literature on digital servitization shows that digital technologies allow manufacturers to provide new value creation and value capture opportunities through monitoring, control, optimization, and autonomous functions (Gebauer et al, 2020;Kohtamäki et al, 2019;Paschou et al, 2020). In other words, digital technologies not only facilitate servitized business models (Arnold et al, 2016;Suppatvech et al, 2019;Vendrell-Herrero et al, 2017), such as outcome business models (Sjödin et al, 2020a;Visnjic et al, 2017) but also contribute to the development of emerging industrial digital platforms with opportunities for value creation and capture that go far beyond traditional products and services (Cenamor et al, 2017;Rajala et al, 2019;Wei et al, 2019).…”
Section: Digital Servitization and Industrial Digital Platformsmentioning
confidence: 99%
“…Recent studies have emphasized the technological infrastructure for servitization and suggested that digital technologies were integral parts of servitization [13]. To cope with servitization, manufacturing firms have increasingly implemented digitalization to deliver services and to create more value for customers [40,41]. Digitalization is the transformation of business models as a result of a fundamental change to core internal procedures by adopting information and communication technologies [42].…”
Section: Servitization and Digitalizationmentioning
confidence: 99%
“…Whereas the digitalization literature emphasizes digital technology as an enabler to business model innovation at the organizational and ecosystem level (Parida et al 2019 ; Linde et al 2021 ), the servitization literature concerns such change in business models for manufacturing firms moving from product to service dominant logic (Baines et al 2009 ; Hyun and Kim 2021 ). Although digital technologies have been an essential ingredient of servitization from its conception, the two literature streams have only recently converged explicitly as digital servitization (Gebauer et al 2021 ).…”
Section: Review Of Literaturementioning
confidence: 99%